2005
DOI: 10.1590/s0100-204x2005000600008
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas de misturas para sherbet de mangaba

Abstract: Resumo -O objetivo deste trabalho foi avaliar a viscosidade, a quantidade de água não congelada (w nc ) e a temperatura de transição vítrea da fração maximamente crioconcentrada (Tg') de misturas para sherbet, e a incorporação de ar (IAr) dos sherbets, com diferentes concentrações de goma guar (0,2% a 0,5%) e polpa de mangaba (21,1%, 25,8% e 28,6% o C e não apresentou diferença entre as amostras. A IAr foi de 20,01% a 40,59%. Sherbets com a mesma concentração de polpa apresentaram valores diferentes desta vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
7
2
3
Order By: Relevance
“…The glass transition is less visible than the endothermic peak because of the greater energy variation involved in the second phenomenon (Sobral et al, 2001); it can be better visualised in an amplified scale (supplementary material). This behaviour is common in high water systems such as those typical of ice cream mixes (Goff et al, 1993;Oliveira et al, 2005). Indeed, the ice creams produced in this study presented humidity between 61 and 67% (wb) (Table 2).…”
Section: Thermal Properties Of Ice Cream Mixesmentioning
confidence: 61%
See 1 more Smart Citation
“…The glass transition is less visible than the endothermic peak because of the greater energy variation involved in the second phenomenon (Sobral et al, 2001); it can be better visualised in an amplified scale (supplementary material). This behaviour is common in high water systems such as those typical of ice cream mixes (Goff et al, 1993;Oliveira et al, 2005). Indeed, the ice creams produced in this study presented humidity between 61 and 67% (wb) (Table 2).…”
Section: Thermal Properties Of Ice Cream Mixesmentioning
confidence: 61%
“…The amount of unfrozen water (w uf ) in the samples was calculated from Equation 1 (Oliveira et al, 2005):…”
Section: Thermal Properties Of Ice Cream Mixesmentioning
confidence: 99%
“…The higher viscosity of the control sample may be due to the smaller air cells present in it . Oliveira et al reported that higher mangaba pulp concentrations increased the apparent viscosity and soluble solid content and also contributed to reducing free water in the mixture, a desirable characteristic in frozen desserts such as ice creams. In the present study, when we increased the KP concentration to 5, 10 and 15% (samples B, C and D respectively), the apparent viscosity decreased owing to the low total solid content of the mixes compared with the control sample.…”
Section: Resultsmentioning
confidence: 99%
“…Mangaba (Hancornia speciosa Gomez) is a typical Cerrado biome fruit widely used in regional gastronomy and has recently attracted increasing interest due to its considerable potentialities which have stimulated its sustainable cultivation in the Brazilian Northeast and West Central Regions (SOUSA et al, 2005). Oliveira et al (2005) used mangaba to prepare sherbet (a product made with water, sugar, fruit, milk solids, stabilizers, and colorings) and observed that higher pulp concentrations increased the apparent viscosity and soluble solids contents, and it also contributed to reduce free water in the mixture, a desirable characteristic in frozen desserts such as ice creams.…”
Section: Introductionmentioning
confidence: 99%